The properties of Green’s functions for one stationary problem with nonlocal boundary conditions - Roman, Svetlana; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2009)
In this paper we research Green’s function properties for stationary problem with four-pointnonlocal boundary conditions. Dependence of these functions on values ξ and γ is investigated. Green’sfunctions graphs with various values ξ and γ are presented.
Keywords: stationary differential problem; Green’s function; nonlocal boundary conditions